Development and validation of a data logger for thermal characterization in laying hen facilities - Letícia C. da S. R. Freitas; Ilda de F. F. Tinôco; Richard S. Gates; Matteo Barbari; Márcia G. L. Cândido; João V. Toledo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The environmental monitoring in animal facilities that includes collected data storage in a robust, practical and feasible way is a constant challenge. The aim of this study was to develop a reliable data logger for monitoring the air temperature and air relative humidity of aviaries and to assess the adequacy of the design using commercially available reference standard instruments. The experimental data logger was installed together with a commercial data logger, a mercury thermometer and a calibrated Vaisala HMP110 air relative humidity probe in a meteorological shelter. Linear regression analysis was performed with the collected air temperature and air relative humidity to develop calibration equations. The Nash-Sutcliffe Index and the relative error were calculated to validate the experimental data logger. The air temperature and the air relative humidity calibration equations presented Nash-Sutcliffe of 0.993 and -0.281 for the commercial data logger, and 0.913 and 0.932 for the experimental data. The mean relative error of the air temperature readings was 3 and 1% and for air relative humidity 5 and 20%, for the experimental and commercial logger, respectively. The experimental data logger reliably stored all collected data without error to the micro-SD card. The experimental data logger can be considered low-cost and sufficiently accurate for monitoring air temperature and air relative humidity in aviaries, presenting field performance very close to the commercial data logger for air temperature measurement, and better performance than the commercial data logger for the measurement of air relative humidity.